2016
DOI: 10.1108/jarhe-01-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Promoting active learning in introductory financial accounting through the flipped classroom design

Abstract: Purpose – The purpose of this paper is to describe a classroom design for introductory financial accounting that promotes active learning through a flipped classroom approach. A course learning management system, white-board voice-over video applications, an online homework manager and online tutorials pre-packaged with the course textbook were all adopted to facilitate the flipped classroom. The in-class sessions were refocussed around active learning strategies, including case analysis, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
3
48
0
3
Order By: Relevance
“…This is more obvious among learners with low prior knowledge (LPK) than those with high prior knowledge (HPK; Mayer, ). Even the few studies that referred to CTML in FCA did not use its principles to design educational multimedia or compare learners' academic achievements for HPK with LPK (Lee & Choi, ; Lento, ; Slemmons et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is more obvious among learners with low prior knowledge (LPK) than those with high prior knowledge (HPK; Mayer, ). Even the few studies that referred to CTML in FCA did not use its principles to design educational multimedia or compare learners' academic achievements for HPK with LPK (Lee & Choi, ; Lento, ; Slemmons et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The project revealed that feedback did not just come from the teacher, as the more experienced students shared their knowledge. Peer and group learning within the flipped approach has been cited as a contributory success factor in the flipped approach (Lento and Blessinger 2016;Hung 2015;Jensen, Kummer and Godoy. 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, these perceptions do not necessarily translate to students' results, and whilst anecdotal evidence suggests that student learning is improved by flipped learning (Azemi, 2013) there is very little objective evidence to support this (Bishop & Verleger, 2013;Findlay-Thompson & Mombourquette, 2014), with the literature producing mixed results. For example, in comparing student results in traditional and flipped learning environments, results have been found to be identical (Findlay-Thompson & Mombourquette, 2014), or not adversely affecting student performance (Mason et al, 2013) whilst others have found students exposed to the flipped learning environment perform better (Lento, 2016;Marcey & Brint, 2012;Kong, 2014).…”
Section: The Flipped Learning Approachmentioning
confidence: 99%